Pengaruh Penggunaan Abu Sekam Padi (Rice Husk Ash) Pada Beton Normal Terhadap Nilai Kuat Tekan - Teguh Haris Santoso (Universitas Pancasakti Tegal, 2021)
This study aims to determine the effect of adding rice husk ash to normal concrete on its compressive strength value. The benefit of this research is to increase knowledge about the effect of rice husk ash which can be used as an effort to reduce the use of Portland cement in concrete. This research method uses an experimental method of an experiment to determine the effect of a variable under study. The location of this research was conducted at the laboratory of PT. Nisajana Hasna Rizqy Tegal. The results of this study are the composition of the mixture of rice husk ash mixture which has the greatest compressive strength value occurs in the mixture of ASP * 10% concrete at 19.84 MPa aged 28 days, the compressive strength value does not reach the planned target of 24 MPa.